An Appraisal Analysis of Interpersonal Metafunction in Tiktok Advertisements - Vadia Fika Munida; Fika Naila Izzati; Azzahrotun Nisa; Lia Roudlotul Jannah; Lala Afrilia (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study explores the interpersonal persuasive strategies used by Indonesian Small and Medium Enterprises (SMEs) in their TikTok video advertisements through the framework of Systemic Functional Linguistics (SFL) and Appraisal Theory. Using a qualitative descriptive approach, three advertisements from different brands, there are Risol Mayo Margo, Petit Bite, and Madam Gie. The data were collected through non-participant observation and documentation by selecting, downloading, and transcribing advertisement videos from each brand’s official TikTok account. The data were then analyzed to examine how Attitude, Graduation, and Engagement resources construct persuasive meaning. The findings reveal three dominant strategies: narrative authenticity, linguistic sincerity, and aesthetic engagement. Risol Mayo Margo emphasizes emotional warmth and authenticity, Petit Bite builds hype and urgency through intensified expressions, while Madam Gie focuses on reassurance and trust through dialogic communication. The study shows that effective TikTok advertising relies not only on visual appeal but also on interpersonal meaning-making that fosters emotional connection, authenticity, and audience engagement.